The Effect of Movie Script Toward Students’ Reading Comprehension - Rismalasari, Rismalasari; Patahuddin, Patahuddin; A, Nasrullah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
Movie script is a medium that can help students in learning to read. The researcher gave a movie script to students to read and understand the content of the story in the movie script that had been distributed and filled in on the kwl sheet about what they knew, wanted to know and what they had learned in the movie script story. Researchers checked each job. The reading comprehension of grade 11 students at SMAN 3 Sidrap is still low due to a lack of motivation to learn to read due to a lack of media that can attract students' interest in reading. To overcome this problem, researchers apply teaching reading using Movie Script media. The purpose of this study was to see the effect of movie scripts on reading comprehension and motivation of 11th grade students of SMAN 3 Sidrap for the 2021/2022 academic year. This study used a pre-experimental method which was only applied to one class. Students were divided into 5 groups of 25 students, after that each group was given a movie script and each group was given the task of understanding the contents of the story and writing their thoughts on the KWL column sheets that had been distributed. The population in this study were 11th grade students of SMAN 3 Sidrap. The research sample is class XI.IPA 1 with a total of 25 people. The results of the data analysis showed that students' reading comprehension increased but not significantly. The results showed that the pre-test got an average score of 57.2 while the post-test got an average score of 76.4. This means that teaching reading comprehension through movie script media is beneficial for some students in understanding reading content. In addition, the post test score is 76.4, higher than the minimum criteria at SMAN 3 Sidrap, which is 70 points. Data analysis using the t-test, the results of the t-test value (0.250) are lower than the t-table (α = 0.05: 1.729). This means that the Null Hypothesis (H0) is accepted and (H1) the Alternative Hypothesis is rejected. The results of the study concluded that teaching reading comprehension through movie script media was able to improve students' reading comprehension but not significantly. However, the results of the questionnaire showed positive results of 60.01% -100% (strongly agreed) that students were interested and motivated in the movie script teaching materials provided.